Time and space scales for measuring urban growth - Anne Bretagnolle; Fabien Paulus; Denise Pumain (Cybergeo)
After the last two centuries of intense and unprecedented urbanization, we need a clear understanding of the ongoing trends of urban growth for a better insight of their possible future. Two main processes are analysed: first, the inter-urban concentration of population, with its consequence being a relative decline of the smallest towns; second, urban sprawl, including a shift of population density from the central part of cities towards their peripheries. Using recent data on population and employment in French urban functional areas, we show that the spatial and temporal framework in which urban growth is computed may considerably alter the results and their consecutive interpretation. When the city is defined as a continuously built-up area (the French agglomération), the measurement of concentration of urban population does not give the same result than when using as a definition the spatial scale of functional urban areas (the French aires urbaines). Similarly, the analysis of the spatial redistribution of population between urban centres, close and outer suburbs are reconsidered under trends of a longer duration and have given very different results, according to the way of defining cities and spaces.